Small-holder Goat Farmer Profile Demographic-based on Financial Aspect in Majene Regency, West Sulawesi Province - Muhammad Iqbal Rivai; Tanrigiling Rasyid (Journal of Global Innovations in Agricultural Sciences)
Generally, goat farming in Majene Regency is traditionally managed, with relatively low average livestock ownership. This study aims to classify the demographic profile based on the R/C ratio value to identify groups of farmers who need special attention. This approach allows for more targeted policy development, resulting in more efficient use of resources, increased profitability, and a positive impact on the economy of goat farmers. The sampling method used the limited population formula, resulting in 123 farmers. A simple random sampling method was used, and the data collection method used a survey technique. K-mean cluster analysis was performed to classify farmers into three groups. The results obtained are in the form of several points described as follows: (1) technical efficiency related to physical strength, (2) business efficiency does not depend on formal education, (3) productive age and experience can increase efficiency, (4) efficiency is not maximized due to traditional management and (5) livelihoods of farmers affect the scale of ownership. This finding emphasizes the need for empowerment for women farmers, such as forming a Farmer Women Group (FWG). For goat farmers who consider traditional methods to optimize efficiency, counseling and training are needed. For goat farmers who consider traditional methods to maximize efficiency, counseling and training are needed. More detail, a pilot or fostered goat farm with easy, efficient and profitable management is needed based on technology so that farmers who still make raising livestock a side job are more confident and switch to focus more on goat breeding activities.